2023
DOI: 10.1101/2023.03.22.533775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individualized Electrode Subset Improves the Calibration Accuracy of an EEG P300-design Brain-Computer Interface for People with Severe Cerebral Palsy

Abstract: Objective: This study examined the effect of individualized electroencephalogram (EEG) electrode location selection for non-invasive P300-design brain-computer interfaces (BCIs) in people with varying severity of cerebral palsy (CP). Approach: A forward selection algorithm was used to select the best performing 8 electrodes (of an available 32) to construct an individualized electrode subset for each participant. BCI accuracy of the individualized subset was compared to accuracy of a widely used default subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Such personalization may also be required at the level of the selection of BCI control features. A recent study by Tou et al (2023) showed that individualized electrode selection in children with severe CP appears to improve the calibration accuracy of BCIs, while this was less the case for children with mild CP, and not beneficial for typically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…Such personalization may also be required at the level of the selection of BCI control features. A recent study by Tou et al (2023) showed that individualized electrode selection in children with severe CP appears to improve the calibration accuracy of BCIs, while this was less the case for children with mild CP, and not beneficial for typically developing children.…”
Section: Discussionmentioning
confidence: 99%